A kind of UV moisture dual curing sealant and preparation method thereof
Through the UV moisture dual-curing sealant composition, the problems of high moisture permeability, shrinkage and thermal expansion coefficient during the curing process are solved by using ultraviolet light and moisture dual-curing technology, and the problems of existing sealant are solved, achieving low moisture permeability and low shrinkage , sealing effect with low thermal expansion coefficient and high bonding strength.
Patent Information
- Application Number
- CN202211434877.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-11-16
AI Technical Summary
The existing electronic equipment sealants have high moisture permeability, large curing shrinkage and thermal expansion coefficient during the curing process, resulting in a decrease in bonding strength and moisture penetration, which damages the internally packaged devices.
UV moisture dual curing sealant composition includes epoxy acrylate prepolymer, rigid cyclic structure-containing epoxy resin prepolymer, alicyclic epoxy compound, oxetane compound, silane-capped polyether, Free radical photoinitiator and cationic photoinitiator achieve sealing effects with low moisture transmission, low shrinkage and low thermal expansion coefficient through dual curing technology of ultraviolet light and moisture.
Low moisture transmission, low shrinkage, low thermal expansion coefficient and high bond strength are achieved, avoiding moisture infiltration and device damage, while reducing the risk of heat release during curing.
Smart Images

Figure GDA0005119395980000121 
Figure GDA0005119395980000131 
Figure GDA0005119395980000132
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives and is used for moisture-proof sealing around OLED or other display screens. Background Art
[0002] With the rapid development of the electronics industry, electronic devices are increasingly moving towards high integration and ultra-thinness. Many optoelectronic devices in electronic devices are moisture sensitive and need to be protected from exposure during their functional life. The usual method is to use an impermeable substrate and an impermeable glass cover or metal cover, and then seal or bond the substrate and cover with a sealant, which is the only material with moisture permeability around moisture-sensitive devices.
[0003] Compositions of epoxides and cationic initiators are widely used in such sealants. For example, patent document WO 2021 / 193576A1 uses aliphatic epoxy resins, oxetane compounds, and bisphenol A epoxy resins, and photothermally cures them under the action of cationic initiators to obtain sealant products. The introduction of aliphatic epoxy resins and oxetane compounds makes them have very low water absorption, but also reduces the adhesion. In addition, these compositions will produce volume shrinkage during the curing reaction. The volume shrinkage during the curing reaction causes voids and microcracks to form in the cured material, thereby reducing the mechanical strength of the material. Especially in some semiconductor packaging and assembly applications, shrinkage causes failure of contact between the adhesive and the substrate, resulting in adhesion failure. More importantly, however, moisture can reach the surface of the substrate through voids and cracks, damaging the internally encapsulated devices.
[0004] Photoinitiated polymerization systems are also increasingly widely used in this type of moisture-proof sealant. On the one hand, it is because of its low energy consumption, lack of solvents, and is safer and more environmentally friendly. On the other hand, it is also because of its relatively lower curing temperature, which can prevent damage to certain heat-sensitive components. So far, the common photoinitiated polymerization systems include photoinitiated free radical polymerization systems and photoinitiated cationic polymerization systems. Among them, free radical polymerization is very dependent on light sources. Once the light source is removed, the reaction stops immediately. Therefore, the design of the general photoinitiated free radical polymerization system makes its reaction very violent and releases a large amount of heat in a short period of time. Photoinitiated cationic polymerization is an active polymerization reaction. Once the polymerization is initiated, the reaction will not stop even if the light source is removed. There is an obvious post-curing reaction, which makes the reaction more thorough. It is called "immortal polymerization". Although the cationic polymerization system has obvious post-curing, which makes the released heat relatively milder, generally a large amount of cationic photoinitiator is still required to promote the complete reaction of the system, and a large amount of heat is still released in a short period of time. On the one hand, the concentrated release of heat still poses a risk of damaging heat-sensitive components. On the other hand, it will also increase the shrinkage rate during the curing reaction, resulting in reduced bonding strength or the formation of voids and microcracks, allowing moisture to pass through the voids and cracks to damage the internal packaged devices. Summary of the invention
[0005] In view of the above defects, the present invention provides an electronic equipment sealant with low moisture permeability, low shrinkage, low thermal expansion coefficient, high bonding strength and mild heat release.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a UV moisture dual curing sealant composition, comprising A) epoxy acrylic prepolymer, B) epoxy resin prepolymer containing rigid ring structure, C) alicyclic epoxy compound, D) oxetane compound, E) silane end-capped polyether, F) alkoxy silane compound, G) free radical photoinitiator, and H) cationic photoinitiator.
[0008] The UV-moisture dual-curing sealant composition may further include 1) other additives.
[0009] 1) Component A: Epoxy acrylate prepolymer
[0010] The epoxy acrylate prepolymer is preferably bisphenol A epoxy acrylate or novolac epoxy acrylate.
[0011] The epoxy acrylate prepolymer preferably has a functionality of 2 or 3, and more preferably has a functionality of 2.
[0012] The epoxy acrylate prepolymer preferably has a viscosity of less than 100,000 mPa.s at 25°C.
[0013] The bisphenol A epoxy acrylate can be selected from DM 127-100, DM 127-TP20, and DM 188 of Double Bond Chemical Co., Ltd., CN 104, CN 110, CN 115, and CN 120 of Sartomer Chemical, LuCure 2651 and LuCure 2655 of Runao Chemical, and 621-100, 6223, 624-100, and 6215-100 of Changxing Chemical.
[0014] The novolac epoxy acrylate can be selected from DM 1636 of Double Bond Chemical Co., Ltd., SP-4010 of Shanghai Showa Polymer Co., Ltd., or 625C-45 of Changxing Chemical.
[0015] The epoxy acrylate prepolymer addition ratio is 5% to 20%, a percentage of the total weight of AF.
[0016] If the epoxy acrylate prepolymer addition amount is lower than the above minimum ratio, the viscosity is still very thin after UV irradiation, and it cannot be well positioned, affecting subsequent construction. If the epoxy acrylate prepolymer addition amount is higher than the above maximum ratio, a large amount of heat is released in a short period of time after UV irradiation, which may cause damage to heat-sensitive components, increase the shrinkage rate during the curing reaction, reduce the bonding strength, or form gaps and microcracks, so that moisture can pass through the gaps and cracks to damage the internal packaged devices.
[0017] On the one hand, the epoxy acrylate prepolymer can be cured after being irradiated with ultraviolet light to increase the viscosity of the sealant product and provide a certain adhesive force, thereby playing a positioning role. On the other hand, it can replace part of component B, thereby reducing the viscosity of the system while achieving better adhesive force.
[0018] If the viscosity of the epoxy acrylate prepolymer at 25° C. is higher than the above maximum value, the effect of reducing the viscosity of the system cannot be achieved.
[0019] 2) Component B: Epoxy resin prepolymer containing rigid ring structure
[0020] The epoxy resin prepolymer containing a rigid ring structure is preferably an epoxy resin prepolymer containing a rigid ring structure having at least two cationically curable epoxy functional groups at the end of the molecular chain, and can be selected from a combination of one or more of naphthalene epoxy resin, fluorene epoxy resin, dicyclopentadiene phenol epoxy resin, and linear phenolic epoxy resin. These epoxy resins contain a rigid polycyclic aromatic hydrocarbon structure, which has the characteristics of high heat resistance, low water absorption, low expansion coefficient, and low shrinkage.
[0021] The addition ratio of component B is 10%-30%, which is a percentage of the total weight of AF.
[0022] These rigid ring structure epoxy resin prepolymers have ultra-low water absorption, low thermal expansion coefficient and low curing shrinkage after curing.
[0023] The naphthalene-type epoxy resin can be selected from HP-4032, HP-4701, HP-4700, HP-4770 of Nippon Ink and Chemicals Co., Ltd., and can also be selected from NC-7300L and NC-7000L of Nippon Kayaku.
[0024] The fluorene epoxy resin can be selected from EX-1010, EX-1020, EX-1030, EX-1040, and EX-1050 produced by Nagase Chemical Technology Co., Ltd.
[0025] The dicyclopentadiene phenol epoxy resin can be selected from SQDN-301, SQDN-302, and SQDN-303 of Jinan Shengquan Group.
[0026] The linear phenolic epoxy resin can be selected from EPALLOY 8220, EPALLOY 8230, EPALLOY 8240, EPALLOY 8250 produced by CVC Thermosetting Special Materials Company, and can also be selected from NPPN-631 and NPPN-638S produced by Nan Ya Company.
[0027] The epoxy resin prepolymer containing a rigid ring structure preferably has a softening point below 80° C., and more preferably has a softening point below 60° C. The sealant products prepared using these epoxy resins have lower viscosity and are easier to construct.
[0028] 3) Component C: alicyclic epoxy compound
[0029] The alicyclic epoxy compounds include alicyclic glycidyl ethers and alicyclic glycidyl esters.
[0030] The alicyclic epoxy compound can be 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester (such as Jiangsu Taitel TTA 21), bis-(3,4-epoxycyclohexylmethyl) adipate (such as Dow Chemical UVR-6128), dicyclopentadiene diepoxide (such as Jiangsu Taitel TTA 27), tetrahydrophthalic acid diglycidyl ester (such as Jiangsu Taitel TTA182), cyclohexane-1,2-dicarboxylic acid diglycidyl ester (such as Jiangsu Taitel TTA184), etc.
[0031] The addition ratio of component C is 10%-40%, which is a percentage of the total weight of AF.
[0032] The epoxy groups of the alicyclic epoxy compound are directly connected to the alicyclic ring to form a tight rigid molecular structure. After curing, the crosslinking density is large, so the thermal deformation temperature is high. Therefore, its curing shrinkage is small, the tensile strength is high, and the thermal stability is good.
[0033] 4) Component D: Oxetane compound
[0034] The oxetane compound refers to a compound containing at least one oxetane group.
[0035] The oxetane compound can be selected from 3-ethyl-3-epoxypropanemethanol (available from Nantong Synasia New Materials Co., Ltd., brand name Syna Epoxy S-101), 3-[oxybismethylene]bis[3-ethyl]oxetane (available from Nantong Synasia New Materials Co., Ltd., brand name Syna Epoxy S-221), methacrylate oxetane (available from Hubei Gurun Technology Co., Ltd.), p-[(3-ethyl-3-oxetanyl)methyl]benzene-1,4-dicarboxylate (available from Hubei Gurun Technology Co., Ltd.), 3-(chloromethyl)-3-ethyloxetane (available from Hubei Gurun Technology Co., Ltd.).
[0036] The viscosity of the oxetane compound is preferably 5 to 500 mPa.s, more preferably 10 to 100 mPa.s.
[0037] Oxetane has a high cationic reaction activity, which can improve the efficiency of the cationic reaction. It has a low viscosity and can reduce the viscosity of the system, playing the role of an active diluent.
[0038] The addition ratio of component D is 10%-30%, which is a percentage of the total weight of AF.
[0039] If the amount of component D added is less than the above minimum ratio, the cationic reaction efficiency is insufficient, the prepared sealant composition has high viscosity, and is difficult to apply. If the amount of component D added is greater than the above maximum ratio, the cationic reaction efficiency is too high, and after ultraviolet light irradiation, a large amount of heat is released in a short period of time, which may cause the risk of damaging heat-sensitive components, and increase the shrinkage rate during the curing reaction, resulting in reduced bonding strength, or forming gaps and microcracks, so that moisture can pass through the gaps and cracks to damage the internally packaged devices.
[0040] 5) The above-mentioned epoxy resin prepolymer containing a rigid ring structure (B), alicyclic epoxy compound (C) and oxetane compound (D) form a continuous sea structure after curing.
[0041] 6) Component E: Silane-terminated polyether
[0042] The silane-terminated polyether has a polyether as a long chain, and both ends are terminated with alkoxy groups (usually hydrolyzable alkoxysilane groups).
[0043] The molecular weight of the silane-terminated polyether is 1000-100000 Da.
[0044] The silane-terminated polyether has a viscosity of 500 to 50,000 mPa.s.
[0045] The silane-terminated polyether may be selected from one or more of CoatOSil MP200 and CoatOSil 1770 of Evonik, STPE-30, STP E-35, XT-55 and XB-502 of Wacker.
[0046] The addition amount of the silane-terminated polyether is 10-30%, as a percentage of the total weight of AF. For example, the addition amount of the silane-terminated polyether can be 15%, 20%, 25%, etc.
[0047] The silane-terminated polyether is cross-linked and cured under the action of moisture to form a bulk structure elastomer with flexible polyether chains between cross-linking points. These bulk structure elastomers are distributed in the continuous sea structure in the form of island structures.
[0048] Optionally, the sealant composition further comprises a moisture curing catalyst for catalyzing the crosslinking and curing of the silane-terminated polyether under the action of moisture, wherein the moisture curing catalyst includes but is not limited to: tin compounds, such as dimethyltin dineodecanoate, stannous octoate, etc.; and titanium compounds, such as tetra(isopropoxy)titanium, tetra(n-butoxy)titanium, tetra(tert-butoxy)titanium, di(isopropoxy)bis(ethyl acetoacetate)titanium, di(isopropoxy)bis(methyl acetoacetate)titanium and di(isopropoxy)bis(acetylacetonate)titanium, etc.
[0049] The moisture curing catalyst is added in an amount of 0 to 0.5% of the total weight of AF. The moisture curing catalyst can be added in an amount of 0, or 0.01% to 0.5%.
[0050] In some embodiments, the silane-terminated polyether can be moisture-cured even without adding a moisture-curing catalyst, because the silane-terminated polyether itself may contain chemicals that can catalyze its moisture curing, and these chemicals may come from the catalyst added during the preparation of the silane-terminated polyether.
[0051] 7) Component F: Alkoxysilane compound
[0052] The alkoxysilane compound has the following general formula R 1 x R 2 y Si(OR 2 ) 4-x-y
[0053] Where R 1 is an allyl glycidyl ether group, R 2 is an alkyl group, and x is an integer from 1 to 2, y is an integer from 0 to 2, and x+y<4.
[0054] The R 2 Preferred are methyl and ethyl.
[0055] The alkoxysilane compound can be selected from γ-glycidyloxypropyltrimethoxysilane (commercially available, such as Momentive A-187, Shin-Etsu Chemical Co., Ltd. KBM-403, Dow Corning Z-6040), γ-glycidyloxypropylmethyltriethoxysilane (commercially available, such as Momentive A-1871, Shin-Etsu Chemical Co., Ltd. KBE-403, Dow Corning Z-6041), γ-glycidyloxypropylmethyldiethoxysilane (commercially available, such as Momentive A-187, Shin-Etsu Chemical Co., Ltd. KBE-402, Dow Corning Z-6042).
[0056] The alkoxysilane compound is added in an amount of 0.1-1% of the total weight of AF.
[0057] If the amount of alkoxysilane added is lower than the above minimum amount, there are too few connection points between the sea structure and the island structure, and the sea structure and the island structure cannot be tightly combined together, which reduces the strength of the sealant; if the amount of alkoxysilane added is higher than the above maximum amount, the connection points between the sea structure and the island structure are too dense, so that the elasticity of the elastomer between the connection points is limited, thereby reducing the toughness of the material.
[0058] 8) Component (G): Free radical photoinitiator
[0059] The composition further comprises a free radical type photoinitiator G. As the photoinitiator, a general commercially available compound can be used, such as α-hydroxy ketone, α,α'-diethoxyacetophenone, 4,4-diethylaminobenzophenone, 2,2-dimethoxy-2-phenyl-acetophenone, 4-isopropylphenyl-2-hydroxy-2-propyl ketone, 1-hydroxycyclohexylphenyl ketone, isopentyl-p-dimethylaminobenzoate, methyl-4-dimethylaminobenzoate, methyl-o-benzoylbenzoate, benzoin, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 2-isopropyl The free radical photoinitiators include thioxanthone, dibenzosuberone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bisacylphosphine oxide, benzophenone (BP), 4-methylbenzophenone, 4-phenylbenzophenone (PBZ), 2,4,6-trimethylbenzophenone, 2-ethylanthraquinone (EAQ), 2-chlorothioxanthone (CTX), 1-chloro-4-propoxythioxanthone (CPTX), 2-isopropylthioxanthone (ITX), 2,4-diethylthioxanthone (DETX), wherein the free radical photoinitiators mentioned can be used alone or in combination of two or more of the listed compounds.
[0060] The free radical photoinitiators used as component (G) in the composition of the invention are preferably activatable by actinic radiation at a wavelength of 200 to 600 nm, particularly preferably 320 to 480 nm. If desired, the photoinitiators can be used in combination with suitable sensitizers.
[0061] The free radical photoinitiator is added in a proportion of 0.1%-5% of the total weight of AF.
[0062] 9) Component H: Cationic photoinitiator
[0063] The cationic photoinitiator is generally selected from a mixture of one or more diaryliodonium fluoride initiators and triarylsulfonium fluoride initiators.
[0064] The cationic photoinitiator may use commercially available compounds, such as Doublecure 1130, Doublecure 1172, Doublecure 1176, Doublecure 1190 from Double Bond Chemical, UV9380C from Momentive, PC2506 from Polyset, SR1012 from Sartomer, Rhodorsil 2074 from Rhodia, and UVI-6974 from Dow Chemical.
[0065] The cationic photoinitiator is added in an amount of 0.1%-0.5% of the total weight of AF.
[0066] If the cationic photoinitiator is added in an amount greater than 0.5%, a large amount of heat will be released in a short period of time after ultraviolet light irradiation, which may cause the risk of damaging heat-sensitive components and increase the shrinkage rate during the curing reaction, thereby reducing the bonding strength or forming voids and microcracks, allowing moisture to pass through the voids and cracks to damage the internally packaged devices; if the cationic photoinitiator is added in an amount less than 0.1%, too few cationic polymerization active centers will be generated after ultraviolet light irradiation, and the post-curing will be too weak, resulting in incomplete final curing of the sealant, insufficient cross-linking, and high moisture permeability.
[0067] Optionally, the sealant composition may further include an auxiliary initiator to improve the initiation efficiency of the cationic photoinitiator and broaden the excitation wavelength of the cationic photoinitiator. The auxiliary initiator may be one or more of benzophenone (BP), 4-methylbenzophenone, 4-phenylbenzophenone (PBZ), 2,4,6-trimethylbenzophenone, 2-ethylanthraquinone (EAQ), 2-chlorothioxanthone (CTX), 1-chloro-4-propoxythioxanthone (CPTX), 2-isopropylthioxanthone (ITX), and 2,4-diethylthioxanthone (DETX).
[0068] In certain embodiments, the co-initiator also acts as a free radical photoinitiator.
[0069] 10) Component I: Other additives
[0070] Optionally, the sealant composition further comprises other additives, such as a leveling agent, a defoaming agent, a wetting and dispersing agent, and the like.
[0071] The leveling agent is preferably one of BYK-UV3510, BYK-333, BYK-307, BYK-399 or BYK-354 produced by BYK Chemical.
[0072] The defoamer is preferably one of BYK-066N, BYK-055, BYK-A535, BYK-054, BYK-088, BYK-1796 or BYK-1799 produced by BYK Chemical.
[0073] The wetting and dispersing agent is preferably one of BYK-W094, BYK-111 or BYK2700 produced by BYK Chemical.
[0074] 11) The present invention provides a method for preparing the above-mentioned UV moisture dual curing sealant composition
[0075] Under the protection of yellow light, add oxetane compound, alicyclic epoxy compound and free radical photoinitiator, cationic photoinitiator in a planetary stirring kettle, mix evenly and dissolve the initiator completely, then add epoxy acrylic prepolymer and epoxy resin prepolymer containing rigid ring structure, stir until completely dissolved, finally add alkoxy silane compound, silane end-capped polyether and other additives, stir for 30min±10min under the protection of nitrogen, disperse the components evenly, remove bubbles in vacuum, and package to obtain the UV moisture dual curing sealant composition. The viscosity of the raw materials, the order of adding the components and the sufficient stirring time can ensure that the island structure is evenly distributed in the sea structure. If the dispersion is uneven, the island structure will not be evenly distributed in the sea structure.
[0076] The technical solution of the present invention is analyzed in more detail below.
[0077] Under the irradiation of ultraviolet light, the epoxy acrylate prepolymer is completely polymerized under the action of a free radical initiator, so that the viscosity of the sealant increases and a certain bonding force is provided to achieve the purpose of positioning; the epoxy resin prepolymer containing a rigid ring structure, the alicyclic epoxy compound, and the oxetane compound undergo cationic polymerization under the action of a cationic initiator. Since the amount of the cationic initiator is relatively small, the entire cationic polymerization process occurs slowly. After the ultraviolet light stops irradiating, under the post-curing action of the cationic initiator, the entire cationic polymerization process is extended to half an hour to several hours to complete; the silane-terminated polyether is cross-linked and cured under the action of moisture, and the entire moisture curing process is completed within several hours to several days. Such a step-curing design makes the entire process release heat slowly and does not release a large amount of heat in a short time, thereby avoiding the risk of damage to heat-sensitive components and reducing the shrinkage rate during the curing reaction.
[0078] After the rigid ring structure epoxy resin prepolymer, alicyclic epoxy compound and oxetane compound are cured, a continuous sea structure is formed. After the silane modified polyether is cured, a body structure elastomer with flexible polyether chains between cross-linking points is formed. These body structure elastomers are distributed in the continuous sea structure in the form of island structures. The glass transition temperature of the sea structure is greater than 130°C, and the glass transition temperature of the island structure is lower than -40°C.
[0079] The allyl glycidyl ether group in the alkoxysilane participates in the curing reaction of the sea structure in a cationic curing manner and connects with the sea structure. The alkoxy group is hydrolyzed into silanol under the action of moisture and participates in the cross-linking curing reaction of the island structure and connects with the island structure, so that the sea structure and the island structure are tightly combined together.
[0080] In the cured product of the sealant, the island structures are preferably uniformly distributed in the sea structure. If the distribution of the island structures is not uniform, when the sealant of the present invention is used to bond and seal electronic equipment, the adhesiveness becomes non-uniform or the storage elastic modulus of the cured product becomes non-uniform. The uniform distribution of the island structures in the sea structure means that there are islands and seas within any 10 μm×10 μm. The cured sealant can be tested by scanning electron microscopy to determine the distribution of the island structures in the sea structure.
[0081] Such a sea-island structure enables the sealant composition of the present invention to have excellent toughness at a high glass transition temperature (greater than 130° C.), thereby making it have a low thermal expansion coefficient and avoiding cracking of the bonding interface with the substrate, which causes a decrease in bonding strength or falling off.
[0082] Compared with the prior art, the present invention has at least the following beneficial effects:
[0083] 1. The step curing design makes the whole process release heat slowly, and will not release a lot of heat in a short time, thus avoiding the risk of damage to heat-sensitive components. In addition, it also reduces the shrinkage rate during the curing reaction.
[0084] 2. After the rigid ring structure epoxy resin prepolymer, alicyclic epoxy compound and oxetane compound are cured, a continuous sea structure is formed. After the silane-modified polyether is cured, a bulk structure elastomer with flexible polyether chains between cross-linking points is formed. These bulk structure elastomers are distributed in the continuous sea structure in the form of island structures. Alkoxysilane containing allyl glycidyl ether group is used as a connector to tightly combine the sea structure and the island structure. Such a sea-island structure design makes the sealant composition of the present invention have excellent toughness at a high glass transition temperature, so that its thermal expansion coefficient is low, and it can avoid the cracking of the bonding interface with the substrate to cause a decrease in bonding strength or falling off, or the sealant is too rigid to form gaps or microcracks under stress, so that moisture can pass through the gaps and cracks to damage the internal packaged devices.
[0085] 3. Use epoxy resin prepolymers and alicyclic epoxy compounds containing rigid ring structures. After curing, they can form a tight rigid molecular structure, so that the thermal deformation temperature is high. Therefore, its curing shrinkage is small, the tensile strength is high, and the thermal stability is good. DETAILED DESCRIPTION
[0086] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0087] Preparation method of UV-moisture dual-curing sealant in various embodiments
[0088] Prepare the raw materials in the amounts shown in Table 1, then add the oxetane compound, the alicyclic epoxy compound, the free radical photoinitiator and the cationic photoinitiator in a planetary stirring kettle under yellow light protection, mix evenly and dissolve the initiator completely, then add the epoxy acrylic prepolymer and the epoxy resin prepolymer containing a rigid ring structure, stir until completely dissolved, finally add the alkoxy silane compound, the silane-terminated polyether and other additives, stir for about 30 minutes under nitrogen protection to evenly disperse the components, vacuum evacuate the bubbles, and package to obtain the UV moisture dual-curing sealant composition.
[0089] Preparation method of the sealant composition of the comparative example: except that some components are not used or the dosage of some components is changed, other conditions are the same as those of the embodiment.
[0090] Table 1 Examples and Comparative Examples Raw material types and amounts (mass, parts)
[0091]
[0092]
[0093] The sealant compositions obtained in each embodiment and comparative example were tested, and the test method was as follows:
[0094] Curing method: LED light with a main wavelength of 395nm and an energy density of 100mW / cm 2 , cure for 30 seconds, and then cure at room temperature 25°C, 50% RH for 7 days.
[0095] Water vapor permeability test: Take an appropriate amount of sample, cure it according to the above curing method, and make a 1mm thick sheet. Determine according to GB / T2679.2.
[0096] Shear strength test: Take an appropriate amount of sample, cure it according to the above curing method, and make glass-PET shear sheets. Measure according to GB / T 7124.
[0097] Hardness test: Take an appropriate amount of sample, and prepare samples according to the above curing method under the above LED light to make 3mm thick rubber blocks. According to GB / T 531.1, test the hardness after UV light exposure for 30s, UV light exposure for 30s and room temperature for 8h, and UV light exposure for 30s and room temperature for 7 days.
[0098] Tg test: Take an appropriate amount of sample, cure it according to the above curing method, and make a 3mm*25mm*10mm rubber strip. Use dynamic thermal mechanical analysis (DMA) to measure it at 5℃ / min and raise the temperature to 200℃.
[0099] Thermal expansion coefficient test: Take an appropriate amount of sample, cure it according to the above curing method, and make a 3mm*5mm*5mm rubber block. Test it by thermomechanical analysis (TMA), and heat it up to 200℃ at 5℃ / min.
[0100] Curing volume shrinkage test: Take an appropriate amount of sample and cure it according to the above curing method. Measure according to ISO 3521.
[0101] The test results are shown in Table 2.
[0102] Table 2 Test results of embodiments and comparative examples
[0103]
[0104]
[0105] According to the sealant formulations and test results of the embodiments and comparative examples, the following conclusions were drawn:
[0106] 1. Embodiments 1-4 are UV-moisture dual-curing sealants, and their hardness indirectly reflects the degree of curing of the colloid. After UV light irradiation, the colloid has a certain strength (see Table 2 UV 30s hardness), and the next process can be carried out immediately without affecting the production efficiency of the product; after UV light irradiation, it is placed at room temperature, and the post-curing of the cationic curing reaction continues, and the hardness of the colloid increases (see Table 2 UV 30s + hardness at room temperature for 8h); moisture curing proceeds slowly in the subsequent process, and moisture curing is complete after being placed at room temperature for 7 days, and the hardness reaches the maximum value (see Table 2 UV 30s + hardness at room temperature for 7 days). Such a step-curing design makes the whole process release heat slowly, and will not release a large amount of heat in a short time, thereby reducing the curing shrinkage, moisture permeability, and expansion coefficient, and increasing the bonding strength.
[0107] 2. Compared with Example 1, after increasing the proportion of the epoxy resin prepolymer containing a rigid ring structure in Example 2, the thermal expansion coefficient and curing shrinkage are lower, and the Tg is higher.
[0108] 3. Example 3: Compared with Example 2, the epoxy resin prepolymer containing a rigid ring structure is a combination of a naphthalene-type epoxy resin and a dicyclopentadiene phenol epoxy resin.
[0109] 4. Example 4: Compared with Example 2, the proportion of epoxy acrylate was changed. After increasing the proportion of epoxy acrylate, the hardness increased after UV irradiation for 30 seconds, and the initial strength of the colloid increased.
[0110] 5. In Comparative Example 1, relative to Example 2, the epoxy resin prepolymer containing a rigid ring structure is replaced with a bisphenol A epoxy resin without a rigid ring structure. As a result, the hardness and Tg are reduced, the thermal expansion coefficient and the curing volume shrinkage rate are increased, and the moisture permeability is increased.
[0111] 6. Comparative Example 2 does not contain alkoxysilane compounds relative to Example 2, and has a lower hardness, an increased volume shrinkage, and an increased moisture permeability.
[0112] 7. Comparative Example 3 does not contain epoxy acrylate prepolymer relative to Example 2. After UV irradiation for 30 seconds, the colloid is still relatively thin (the hardness is not tested because the colloid is thin after UV 30 seconds), and the positioning effect cannot be achieved.
[0113] 8. Comparative Example 4 does not contain silane-terminated polyether relative to Example 2, and cannot form an island structure. It reaches the maximum hardness after UV curing and releases heat quickly. After complete curing, the bonding surface falls off due to excessive rigidity. Since it is not bonded, there is no shear strength and test moisture permeability.
[0114] 9. In Comparative Example 5, the amount of cationic photoinitiator is increased relative to that in Example 2. After 30 seconds of UV irradiation, heat release is severe. The hardness after 30 seconds of UV irradiation and after 30 seconds of UV irradiation + 8 hours of room temperature are slightly different. The post-curing of the cationic curing reaction is not obvious (because the cationic curing reaction is more complete after UV irradiation).
[0115] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, it should be understood that those skilled in the art can design many other modifications and implementations, which will fall within the scope and spirit of the principles disclosed in the present application. More specifically, within the scope disclosed in the present application, multiple variations and improvements can be made to the components and / or layout of the subject combination layout. In addition to the variations and improvements made to the components and / or layout, other uses will also be apparent to those skilled in the art.
Claims
1. A UV moisture dual curing sealant, characterized in that: Calculated by mass content, its components include: A) epoxy acrylate prepolymer, which is 5% to 20% of the total mass of components A) to F); B) an epoxy resin prepolymer containing a rigid ring structure, which accounts for 10% to 30% of the total mass of components A) to F); C) alicyclic epoxy compound, which is 10% to 40% by weight of the total weight of components A) to F); D) an oxetane compound, which is 10% to 30% of the total mass of components A) to F); E) silane-terminated polyether, which is 10% to 30% of the total mass of components A) to F); F) an alkoxysilane compound, which is 0.1 to 1% of the total mass of components A) to F); G) a free radical photoinitiator, which is 0.1% to 5% by weight of the total weight of components A) to F); H) cationic photoinitiator, 0.1% to 0.5% by weight of the total weight of components A) to F); The B) rigid ring structure-containing epoxy resin prepolymer is selected from one or more combinations of naphthalene epoxy resin, fluorene epoxy resin, dicyclopentadiene phenol epoxy resin and linear phenolic epoxy resin.
2. The UV-moisture dual-curing sealant according to claim 1, characterized in that: The epoxy acrylate prepolymer is bisphenol A epoxy acrylate or novolac epoxy acrylate, and the functionality of the epoxy acrylate prepolymer is 2 or 3.
3. The UV moisture dual curing sealant according to claim 1, characterized in that: The alicyclic epoxy compound is an alicyclic glycidyl ether or an alicyclic glycidyl ester.
4. The UV-moisture dual-curing sealant according to claim 1, characterized in that: The oxetane compound is selected from a combination of one or more of 3-ethyl-3-epoxypropanemethanol, 3-[oxybismethylene]bis[3-ethyl]oxetane, methacrylate oxetane, p-[(3-ethyl-3-oxetanyl)methyl]benzene-1,4-dicarboxylate, and 3-(chloromethyl)-3-ethyloxetane; the viscosity of the oxetane compound is 5 to 500 mPa.s.
5. The UV moisture dual curing sealant according to claim 1, characterized in that: The silane-terminated polyether has a polyether long chain and is terminated at both ends with alkoxy groups, has a molecular weight of 1000 to 100000 Da, and a viscosity of 500 to 50000 mPa.s.
6. The UV-moisture dual-curing sealant according to claim 1, characterized in that: The alkoxysilane compound has the following general formula R 1 x R 2 y Si(OR 2 ) 4-x-y , where R 1 is an allyl glycidyl ether group, R 2 is an alkyl group, and x is an integer from 1 to 2, y is an integer from 0 to 2, and x+y<4.
7. The UV-moisture dual-curing sealant according to claim 1, characterized in that: The free radical photoinitiator is selected from α-hydroxy ketone, α, α'-diethoxyacetophenone, 4,4-diethylaminobenzophenone, 2,2-dimethoxy-2-phenyl-acetophenone, 4-isopropylphenyl-2-hydroxy-2-propyl ketone, 1-hydroxycyclohexylphenylketone, isopentyl-p-dimethylaminobenzoate, methyl-4-dimethylaminobenzoate, methyl-o-benzoylbenzoate, benzoin, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2-Hydroxy-2-methyl-1-phenylpropane-1-one, 2-isopropylthioxanthone, dibenzosuberone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bisacylphosphine oxide, benzophenone, 4-methylbenzophenone, 4-phenylbenzophenone, 2,4,6-trimethylbenzophenone, 2-ethylanthraquinone, 2-chlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-isopropylthioxanthone, 2,4-diethylthioxanthone or a combination of more thereof.
8. The UV-moisture dual-curing sealant according to claim 1, characterized in that: The cationic photoinitiator is selected from a mixture of one or more diaryliodonium fluoride initiators and triarylsulfonium fluoride initiators.
9. The method for preparing the UV-moisture dual-curing sealant according to any one of claims 1 to 8, characterized in that: In an environment protected by yellow light, an oxetane compound, an alicyclic epoxy compound, a free radical photoinitiator and a cationic photoinitiator are added to a planetary stirring kettle and mixed evenly to make the initiator completely dissolved, and then an epoxy acrylate prepolymer and an epoxy resin prepolymer containing a rigid ring structure are added and stirred until completely dissolved, and finally an alkoxysilane compound, a silane-terminated polyether and other additives are added, wherein the other additives include a leveling agent, a defoaming agent and a wetting and dispersing agent, and the mixture is stirred for 30 min±10 min in an environment protected by nitrogen to make the components evenly dispersed, and the mixture is vacuum-defoamed and packaged to obtain the UV moisture dual-curing sealant composition.
Citation Information
Patent Citations
Dual-curable adhesive composition
WO2021193576A1
Low-viscosity liquid radiation curable dental aligner mold resin compositions for additive manufacturing
CN104345562A
Ultraviolet light and moisture dual-curable composition as well as preparation method and application thereof
CN111471425A